Ergonomic Sofa Intervention in Improving Mother's Posture in Kangaroo Mother Care - Syawal Kamiluddin Saptaputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
Posture that is not ergonomic when the mother performs the Kangaroo Mother Care (KMC) has the potential to cause musculoskeletal complaints and fatigue. The purpose of this study was to analyze differences in body posture (RULA scores) between mothers who used an ergonomic sofa during PMK (intervention group) and mothers who used chairs available at XYZ Hospital during KMC (control group). The study design is an experimental controlled group design which aims to assess the effect of the independent variables on the dependent variable by involving the intervention group and the control group. The research subjects consisted of 54 people consisting of 30 people in the intervention group and 24 people in the control group. The research was conducted in the kangaroo method treatment room at X Hospital. Based on the Mann-Whitney test, the results obtained were p value = 0.000. Because the p value ≤ 0.05, it can be concluded that there are differences in body posture between mothers who use PMK ergonomic sofas (intervention group) and mothers who use chairs available at the hospital (control group). The role of ergonomic interventions is proven to provide benefits for improving posture in doing KMC